8x-3=8(x-5)

Simple and best practice solution for 8x-3=8(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3=8(x-5) equation:


Simplifying
8x + -3 = 8(x + -5)

Reorder the terms:
-3 + 8x = 8(x + -5)

Reorder the terms:
-3 + 8x = 8(-5 + x)
-3 + 8x = (-5 * 8 + x * 8)
-3 + 8x = (-40 + 8x)

Add '-8x' to each side of the equation.
-3 + 8x + -8x = -40 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 + 0 = -40 + 8x + -8x
-3 = -40 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 = -40 + 0
-3 = -40

Solving
-3 = -40

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4(1-3p)=-4-2(-p-5) | | x/4=11 | | 12x-83=6x+121 | | -(3x-7)=24 | | 2v-5=-10 | | (x-3)(1-x)=1 | | 3(6-x)=3 | | 12+8x-12x+6=-122 | | 4j=3.6 | | 3(y+2)+y=15-(y-4) | | 6p-6=7p-7 | | 25x+10y=405 | | 3(7-x)=12 | | 8=-4(3x-4) | | -x-6x+7=42 | | 9-3(x-4)=36 | | -62=5x+3 | | 18+2x/3=16 | | 24=(2x-3) | | 3w-3=4w+8 | | 4(7-x)=4 | | (78+x)+x=434 | | 4.9t^2-13.5t=66 | | 3n=-27 | | 4x^2+18x+14=0 | | -8+6x=38 | | 22x*15*13x= | | 0.6x+3-2x=7x+3 | | 4x-6=6(x+2)+8 | | 9x-4=2x-3 | | 8b+6(-6-2b)=4+b | | x-5+x-5+x-5+x-5=12+x+x |

Equations solver categories